Bacterial Meningitis in Children: Neurological Complications, Associated Risk Factors, and Prevention - Abdulwahed Zainel; Hana Mitchell; Manish Sadarangani (Microorganisms, 2021)
Bacterial meningitis is a devastating infection, with a case fatality rate of up to 30% and 50% of survivors developing neurological complications. These include short-term complications such as focal neurological deficit and subdural effusion, and long-term complications such as hearing loss, seizures, cognitive impairment and hydrocephalus. Complications develop due to bacterial toxin release and the host immune response, which lead to neuronal damage. Factors associated with increased risk of developing neurological complications include young age, delayed presentation and Streptococcus pneumoniae as an etiologic agent. Vaccination is the primary method of preventing bacterial meningitis and therefore its complications. There are three vaccine preventable causes: Haemophilus influenzae type b (Hib), S. pneumoniae, and Neisseria meningitidis. Starting antibiotics without delay is also critical to reduce the risk of neurological complications. Additionally, early adjuvant corticosteroid use in Hib meningitis reduces the risk of hearing loss and severe neurological complications.